2013
DOI: 10.1039/c3ra40950c
|View full text |Cite
|
Sign up to set email alerts
|

Novel cationic fullerene derivatized s-triazine scaffolds as photoinduced DNA cleavage agents: design, synthesis, biological evaluation and computational investigation

Abstract: A series of novel cationic fullerene (C 60 ) derivatives, bearing substituted s-triazine moiety as a side arm, synthesized by using the 1,3 dipolar cycloaddition reaction of C 60 with azomethine ylides generated from the corresponding Schiff bases of substituted s-triazine is reported. All the synthesized compounds were characterized by elemental analysis, FT-IR, 1 H NMR, 13 C NMR and ESI-MS. The compounds 7a, 7d, 7e and 7f cleaved the supercoiled pBR322 DNA into nicked form efficiently upon visible light irra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Therefore, one helical pitch of DNA (3.4 nm) can accommodate three fullerene units or a cluster containing 5–8 fullerenes. On the basis of the atomistic molecular simulation, it was found that the groove binding nature and intrinsic rich π-surface of fullerenes are the main driving force for their ability to self-assemble with DNA. , The suitable functionalization of fullerene with intercalating and cationic groups can make them more accessible to interact with the DNA backbone through electrostatic and van der Waals interactions. For example, Cassell et al studied the assembly of a cationic fullerene derivative, C 60 - N,N -dimethylpyrrolidinium iodide on DNA, in which they showed effective interactions between DNA and fullerene can lead to DNA supercoiling, as can be seen in the transmission electron microscopy (TEM) image (Figure A) .…”
Section: Fullerene-dna Hybrid Materialsmentioning
confidence: 99%
“…Therefore, one helical pitch of DNA (3.4 nm) can accommodate three fullerene units or a cluster containing 5–8 fullerenes. On the basis of the atomistic molecular simulation, it was found that the groove binding nature and intrinsic rich π-surface of fullerenes are the main driving force for their ability to self-assemble with DNA. , The suitable functionalization of fullerene with intercalating and cationic groups can make them more accessible to interact with the DNA backbone through electrostatic and van der Waals interactions. For example, Cassell et al studied the assembly of a cationic fullerene derivative, C 60 - N,N -dimethylpyrrolidinium iodide on DNA, in which they showed effective interactions between DNA and fullerene can lead to DNA supercoiling, as can be seen in the transmission electron microscopy (TEM) image (Figure A) .…”
Section: Fullerene-dna Hybrid Materialsmentioning
confidence: 99%
“…Similarly, the tandem iminium condensation/thermal decarboxylation reaction manifold (via carboxylic acids 278 , Scheme ) is a popular method for in situ preparation of N -alkyl azomethine ylides. In 1993, Prato and co-workers demonstrated that C 60 could be converted to the corresponding pyrrolidine by 1,3-dipolar cycloaddition with the N -methyl azomethine ylide generated via thermal decarboxylation of the iminium formed by condensation between sarcosine ( N -methlyglycine) and formaldehyde (Scheme ). This so-called “Prato reaction”, and variations thereof, have since been applied toward the functionalization of fullerenes, graphene and single-walled carbon nanotubes and nanohorns, …”
Section: Azomethine Ylidesmentioning
confidence: 99%
“…Cationic porphyrin not only enhanced the solubility of C 60 , but also strengthened the affinity to DNA . s‐Triazine scaffolds were attached to ameliorate the hydrophilicity of C 60 and bring C 60 to the DNA minor groove . Furthermore, sugar‐, protein‐, and polymer‐based C 60 derivatives were applied as well.…”
Section: Figurementioning
confidence: 99%